Treatment of an Intractable Forefoot Ulcer Using Realignment Osteotomy in a Patient with Rheumatoid Arthritis. (27th July 2020) - Imai, Makoto; Kondo, Naoki; Kumazaki, Rei; Endo, Naoto
Abstract : Forefoot deformities are common among patients with rheumatoid arthritis (RA). Herein, we describe a case of intractable ulceration on the dorsomedial aspect of the right 5 th digit, secondary to forefoot deformity, in a 76-year-old woman with a 35-year history of RA. The ulcer was due to a persistent subcutaneous infection. Although the infection was controllable with antibiotics, there was concern of relapse because of the abnormal pressure on the skin due to an overlap of the 4 th and 5 th digits. We proceeded with surgical correction of the forefoot alignment, including shortening oblique osteotomy of metatarsals 2 through 5, rather than amputation of the 5 th digit. Following surgery, targeted antibiotic treatment was provided. The postoperative course was unremarkable, and the patient recovered weight-bearing function without recurrence of pain or ulceration. Forefoot realignment is a feasible option that should be considered for treating intractable foot pain and ulceration secondary to long-lasting RA.